Electronic Properties of Hydrogenated Graphene-Like Materials Under Strains. Issue 1658 (22nd May 2014) - Mihara, K.; Shintani, K.
ABSTRACT: The electronic band structures of the hydrogenated graphene-like materials, graphane, silicane, and germanane, under tensile strains are calculated using first-principles calculation. The imposed tensile strain is in either the armchair or zigzag direction in the honeycomb lattice. It is found that the band gap of graphane gradually increases with the increase of the strain, whereas the band gaps of silicane and germanane decrease with the increase of the strain. There is little effect of the direction of the imposed strain on such strain dependences.